AN EXAMINATION OF CULTURAL VALUES ON THE INTELLECTUAL SIDE OF RANI'S CHARACTER IN THE NOVEL NEGERI SERIBU BINTANG BY ARIE KOMALASARI: TELAAH NILAI-NILAI KULTURAL PADA SISI INTELEKTUAL TOKOH RANI PADA NOVEL NEGERI SERIBU BINTANG KARYA ARIE KOMALASARI - Dwianita Conny Palar; Krisdo Paeng; Dina Chatrina Magdalena Rottie (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research is an effort to uncover the cultural values instilled in the character Rani in the Novel Negeri Seribu Bintang by Arie Komalasari through one of the aspects of her personality, namely intellectual. This study uses a qualitative descriptive approach with data collection techniques in the form of reading and recording techniques with literature study methods. The source of the data clearly comes from the Novel Negeri Seribu Bintang by Arie Komalasari. The data taken is in the form of explanations related to the role, character, and personality of the character Rani in the novel based on the intellectual aspects possessed by the character. The results of this study will show how the cultural background of this Rani character shapes her intellectual abilities which are presented in the perspective of Psychological Anthropology. The role of Rani's character is also central in supporting the dynamics of the storyline of this novel. In addition to being a character who is described as a charismatic female character, the intellectual side of this character is also a component that supports the storyline of this novel. The intellectual side possessed by Rani's character is inseparable from her cultural background who was born in an environment of educated people who then formed her personality character in building the plot of this novel. This study also seeks to provide a descriptive explanation of what cultural values make Rani's character a figure who has intellectual intelligence.